Characterization of Blood Volume Space and Mitochondrial Activity in Functional Renal Cells⁎. Issue 19 (2018) - McCarroll, Matthew J.; Clermont, Gilles; Gomez, Hernando; Swigon, David; Parker, Robert S.
Abstract: Renal function can become compromised in the event of shock, leading to acute kidney injury (AKI). As a result, microcirculatory dysfunction and disruption of oxygen homeostastis is observed, which leads to a shift in mitochondrial bioenergetics. These events can be studied by assessing the functionality in healthy, normal states and diseased states. Characterization of the spatial heterogeneity of mitochondrial activity and capillary blood volume space in healthy renal cells was performed using intravital multi-photon microscopy. The developed metrics that were used for depiction and quantification of the physiologic normal state can be applied to a diseased state, allowing the extent of microcirculatory dysfunction to be observed and evaluated.